Effort to Improve Backhand Service Using Drill Variation Method in Extracellular Badminton at SMA Negeri 28 Tangerang District - Agus Prastiyo; Setio Nugroho; Rizki Aminudin (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this research is to improve the backhand service using the drill variant method in the extracurricular activities of SMA Negeri 28, Tangerang Regency. This study uses a quantitative approach to the experimental method. This research is located at SMA Negeri 28, Tangerang Regency, with a total of 23 students. This population was taken using a total sampling technique. This research instrument used drill variations. Data analysis techniques used pretest and posttest design. The results of this study were an average pretest of 6.57 and for a post test of 7.57. The results of the data obtained from this study are an increase in value (2-tailed) 0.00 less than the level of increase (a) = 0.05, then H0 is rejected and H1 is accepted. It can be concluded that the drill variation method can affect serviceability. backhand at Sman 28 extracurricular, Tangerang Regency